Uji Efektivitas Ekstrak Daun Kamboja (Plumeria acuminata) Terhadap Pertumbuhan Jamur (Curvularia sp.) Pada Tanaman Kelapa Sawit (Elais guineeis Jacq.): Uji Efektivitas Ekstrak Daun Kamboja (Plumeria acuminata) Terhadap Pertumbuhan Jamur (Curvularia sp.) Pada Tanaman Kelapa Sawit (Elais guineeis Jacq.) - Daryanti; Siti Mardhika Sari; Haryuni; Achmad Fatchul Aziez; Sapto Priyadi; Teguh Supriyadi; Sutha Adam Aditya Utama (JURNAL ILMIAH AGRINECA, 2026)
This study aimed to evaluate the effect of frangipani leaf (Plumeria acuminata) extract on the in vitro growth of Curvularia sp. isolated from oil palm (Elaeis guineensis Jacq.) and to determine the most effective extract concentration for inhibiting fungal growth. The experiment was conducted using a Completely Randomized Design (CRD) consisting of five treatments: 0 g (control), 10 g, 20 g, 30 g, and 40 g of frangipani leaf extract, with four replications. The observed parameters included colony length, colony width, and colony diameter, which were measured on the seventh day after inoculation. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level. Results showed that frangipani leaf extract significantly affected the growth of Curvularia sp. The 30 g extract concentration exhibited the strongest antifungal activity by producing the smallest colony size, whereas lower concentrations were less effective and a higher concentration (40 g) showed reduced inhibitory activity. The antifungal effect is attributed to the presence of bioactive compounds, including flavonoids, tannins, saponins, and alkaloids, which interfere with fungal cell structure and metabolism. These findings indicate that frangipani leaf extract has promising potential as an environmentally friendly botanical fungicide for sustainable oil palm disease management.